Jimmy Carter's Blood-Drenched Legacy (CounterPunch.org, 2015)
A few days ago former President Jimmy Carter announced that he has cancer and it is spreading. While it would be premature to assume this spells the end for the 90-year-old, it does present an opportunity to take stock of the tenure of a President who, like the current occupant of the White House, entered office with a promise to respect human rights, but failed miserably when given the opportunity to do so. Carter just last month published a memoir about his "Full Life." Others have begun to look back at his four years as President. David Macaray, writing in CounterPunch on 8/14/15, noted that despite his reputation as a President so hapless his fellow Democrats tried to knock him off in a primary, “a closer look shows that Carter accomplished some fairly important things during his single term in office - things that, given the near-paralytic gridlock that defines today’s politics, seem all the more impressive in hindsight.” More